A multicenter randomized placebo controlled trial of rifampin to reduce pedal amputations for osteomyelitis in veterans with diabetes (VA INTREPID) - Bessesen, Mary T. (BMC Infect Dis, 2020)
BACKGROUND: The prevalence of diabetes mellitus continues to inexorably rise in the United States and throughout the world. Lower limb amputations are a devastating comorbid complication of diabetes mellitus. Osteomyelitis increases the risk of amputation fourfold and commonly presages death. Antimicrobial therapy for diabetic foot osteomyelitis (DFO) varies greatly, indicating that high quality data are needed to inform clinical decision making. Several small trials have indicated that the addition of rifampin to backbone antimicrobial regimens for osteomyelitis outside the setting of the diabetic foot results in 28 to 42% higher cure rates. METHODS/DESIGN: This is a prospective, randomized, double-blind investigation of the addition of 6 weeks of rifampin, 600 mg daily, vs. matched placebo (riboflavin) to standard-of-care, backbone antimicrobial therapy for DFO. The study population are patients enrolled in Veteran Health Administration (VHA), ages ≥18 and ≤ 89 years with diabetes mellitus and definite or probable osteomyelitis of the foot for whom an extended course of oral or intravenous antibiotics is planned. The primary endpoint is amputation-free survival. The primary hypothesis is that using rifampin as adjunctive therapy will lower the hazard rate compared with the group that does not use rifampin as adjunctive therapy. The primary hypothesis will be tested by means of a two-sided log-rank test with a 5% significance level. The test has 90% power to detect a hazard ratio of 0.67 or lower with a total of 880 study participants followed on average for 1.8 years. DISCUSSION: VA INTREPID will test if a rifampin-adjunctive antibiotic regimen increases amputation-free survival in patients seeking care in the VHA with DFO. A positive finding and its adoption by clinicians would reduce lower extremity amputations and their associated physical and emotional impact and reduce mortality for Veterans and for the general population with diabetic foot osteomyelitis. Given that rifampin-adjunctive regimens are currently employed for therapy for the majority of DFO cases in Europe, and only in a small minority of cases in the United States, the trial results will impact therapeutic decisions, even if the null hypothesis is not rejected. TRIAL REGISTRATION: Registered January 6, 2017 at ClinicalTrials.gov, NCT03012529.